PENGARUH BAURAN PEMASARAN JASA TERHADAP MINAT NASABAH DALAM MENABUNG PADA BANK BSI KC MADIUN AGUS SALIM - Shintia Wulandari; Ratna Yunita (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Bank BSI KC Madiun Agus Salim is still not popular with the public. One of the factors is customers' ignorance about the concepts and products offered by Bank BSI KC Madiun Agus Salim. The main aim of this research is to test and analyze whether the service marketing mix influences customer interest in saving at BSI KC Madiun Agus Salim bank. This research is quantitative research. The population in this research is all BSI KC Madiun Agus Salim bank customers in 2023, totaling 13,829 customers. The sample in this research was 100 customers. The data collection method uses a questionnaire. Data analysis techniques use classical assumption tests, multiple linear regression analysis tests, hypothesis tests and coefficient of determination tests. The research results show that the variables product, price, promotion, place, people, process and physical evidence have a positive and significant effect on customer interest in saving at Bank BSI KC Madiun Agus Salim.